A comparative study of law and practice of arbitration in Kenya, Nigeria and Zimbabwe, with particular reference to current problems in Kenya - Torgbor, Edward Nii Adja (Stellenbosch University, 2013)
Arbitration as a mode of dispute settlement has been growing steadily all over the world. The momentum for commercial arbitration in particular was provided by the 1985 UNCITRAL Model Law on International Commercial Arbitration (“the Model Law”). Legislation based on the Model Law has been enacted in many countries. The arbitration laws of three of these countries, Kenya, Nigeria and Zimbabwe, are selected for consideration in this dissertation because of their common origins, similar statutes, similar problems, shared experiences, and their regional distribution. As the writer’s arbitration practice is based in Kenya, that jurisdiction is the primary, albeit not the only, source and foundation for this work, the focal point of reference and the citations from the law and practice incorporated in this research. The work consists of three chapters. Chapter one is a brief introduction and an overview of arbitration. This is followed by the statement of the research question, the justification for the research, methodology and the structure and content of the dissertation. Chapter two describes the legal and contextual framework for the investigation of the research questions in the selected jurisdictions of Kenya, Nigeria and Zimbabwe. Customary Law arbitration is included as a significant feature of African arbitration law. The UNCITRAL Model Law, the Arbitration Act, 1995 (Kenya), the Arbitration and Conciliation Act, 1988 (Nigeria), the Arbitration Act, 1996 (Zimbabwe), the Arbitration Act, 1996 (England), and the South African Draft Arbitration Bill are all used as legislative or statutory points of reference in the discussion of the research questions. Chapter 3 contains the main focus of the dissertation in which six recurrent arbitration problems in Kenya are discussed in the context of domestic arbitration. The research investigates (i) the illusiveness of consent as the basis for consensual arbitration (ii) jurisdictional challenges (iii) the procedural powers of the arbitral tribunal (iv) the disruptive effect of adjournments and postponements on the arbitral process (v) constraints on the granting of interim relief and (vi) the enforcement of the arbitral award. Original, creative and innovative proposals in response to these problems include: the express legislative recognition of the manifestation of consent in both the verbal and written forms of the arbitration agreement, the use of the constructive dispute resolution technique, statutory recognition of customary law arbitration, the use of an expedited arbitration procedure, the award of exemplary and punitive damages in arbitration, a code of sanctions to facilitate the arbitration process, and a simplified method of enforcement and execution of the arbitral award. The dissertation concludes with reflections on the future of arbitration in Africa, and the need for modernization and harmonization of arbitration laws for peaceful resolution of disputes and serious conflicts across Africa. The aim of this study is best illustrated by a short story: In the early nineties there was a man, untrained in any known discipline, who strutted court corridors, trade centres and market places, carrying a placard advertising himself to lawyers, traders and marketers as “An Arbitrator and Private Judge”. He attracted business, charged a handsome percentage fee on the value of the claim, was duly paid, until officialdom caught up with him and put paid to his burgeoning career as “Arbitrator-Judge”. But the reckless enthusiasm spawned by his wit and imagination, and the idiosyncratic practices in dispute resolution persisted and are manifest in Kenyan arbitration culture today. The need to remove bad practices, avoidable impediments, and inefficiency in the arbitration culture of Kenya in order to make its procedures and processes more efficacious, is the heart of this study.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration and award; Comparative law; Dispute resolution; Kenya; Nigeria; Zimbabwe